Length and Weight Relationship, Condition Factor, and Morphometric Characteristics of Eleven Freshwater Fish Species in Koto Panjang Reservoir, Indonesia - Azrita Azrita; Hafrijal Syandri; Netti Aryani (International Journal of Zoology)
This study analyzes the species composition, length–weight relationship (LWR), condition factor, and morphometric and meristic characteristics of eleven freshwater fish species in Kota Panjang Reservoir, Indonesia. Fresh specimens were collected from September 2023 to February 2024. Results show that among the sampled species, two belong to Order Anabantiformes, three to Order Siluriformes, and six to Order Cypriniformes. The Order Siluriformes has the lowest species composition, with Hemibagrus wyckii at 3.09%, while the Order Cypriniformes has the highest, with Barbonymus schwanefeldii at 15.25%. The LWR coefficient b ranges from 1.693 to 3.151. Of the species studied, only Hemisilurus heterorhynchus (b = 2.174), Clarias teijsmanni (b = 2.046), Anabas testudineus (b = 2.375), Labiobarbus festivus (b = 2.305), and Rasbora argyrotaenia (b = 1.693) fall outside the expected range of 2.5 < b less than < 3.5. One species exhibits a positive allometric growth (+), seven show a negative allometric growth (−), and three display an isometric growth (I). Fulton’s condition factor (Kc) averages between 0.73 ± 0.15 and 4.96 ± 0.63, indicating morphological variation. The allometric condition factor (Ka) ranges from 0.87 ± 0.18 to 26.25 ± 4.05, reflecting differences in resource availability and competition. Relative condition factor (Kn) values range from 1.00 ± 0.09 to 2.51 ± 0.55, indicating good growth. Morphometric analysis shows that Rasbora argyrotaenia has the smallest average total length, head length, and body depth, while Hemibagrus wyckii has the largest. The results provide new data on the LWR, condition factor, and morphometric characteristics of eleven selected freshwater fish species in Kota Panjang Reservoir, Indonesia, and offer up-to-date information on the remaining species in the study area. These findings could have a significant impact on species stock assessments and help identify priority species for domestication.